Environmental enrichment for the early larval stages of Acipenser baerii in captive environments - M. L. Matela; V. Serra; C. Bazzocchi; S. Modina; A. Di Giancamillo (Soc. It. delle Scienze Veterinarie, 2021)
The Siberian sturgeon, Acipenser baerii Brandt 1869, is included in the IUCN Red Data List. Taking into account the continuous decrease of its natural populations, it is necessary to gather as much information as possible in order to better manage the populations and to enhance farming practises. Larval stages are particularly sensitive to environmental conditions, as these can affect survival and potential growth (Johnston, 2006). In fish destined to production, a suitable environment is of great importance for growth efficiency at harvest. Environmental enrichment is considered to improve biological functioning of captive animals by improving their psychological and behavioural needs. Little information is available on habitat preferences of the free embryos of Acipenser baerii upon hatch. The aim of this study was to assess the environmental enrichment without compromising larval morpho-functional aspects. After hatching and throughout the endogenous feeding period, larvae were reared in two types of substrate (Bioballs type 1 – BB1 and Bioball type 2 - BB2) vs. no substrate (CTR). Behavioural, larval growth parameters (weight and length) and histometrical analyses were studied in order to evaluate muscle development. The analysis of myogenesis and stress were carried out through the use of Real Time PCR, evaluating the relative expression of a pool of genes: Myod, Myog and Mrf4 (involved in myogenesis), Igf2 (involved in growth), Hsp70, Hsp90α, Hsp90β and Glut2 (markers of cells exposed to high stress conditions). This study was approved by the Ethic Committee of the University of Milan (OPBA_15_2018). Larvae reared with BB1, when compared to those reared with BB2 or CTR, were heavier and longer at the end of the trial, and histometrical analyses showed larger areas of total muscle area, slow muscle area and fast muscle area (P<0.05). This is in accordance with studies performed with other species of sturgeon (Baker et al., 2014; Boucher et al., 2017). Moreover, CTR larvae showed an acceleration of muscle ...